The re-opening of judicial proceedings in the Armenian law and practice following the judgments of the European court of human rights - Asatryan, Artak (Bulletin of Yerevan University C: Jurisprudence, 2023)
The Convention for the Protection of Human Rights and Fundamental Freedoms (hereinafter referred to as the Convention) guarantees a number of rights and freedoms that the states that have ratified the Convention are obliged to respect in the territories under their jurisdiction. Regarding violations recorded by the European Court of Human Rights (hereinafter referred to as the ECtHR) created on the basis of the Convention, there is often a need to reopen judicial cases at the domestic level. The importance of this process lies in its central place in the execution system of the ECtHR’s judgments and in some cases is considered as the only way to restore the violated rights.Within the framework of this article, the legislation and practice of the Republic of Armenia regarding the reopening of judicialcases following the judgments of the ECtHR were studied. In particular, the relevant legal regulations of RA criminal procedure, RA civil procedure, RA administrative procedure codes and other legal acts were analyzed. As a result of the comprehensive studies carried out in the article, the gaps, shortcomings and uncertainties of the RA legislation and practice in the discussed field were highlighted, and relevant recommendations were made to fill, eliminate or clarify them.
Keywords: Execution of ECtHR judgments; reopening of judicial cases; revision of judicial cases; legislation of reopening of judicial cases; practice of reopening of judicial cases; flaws in reopening legislation; practical issues of reopening of judicial cases